0625 Characterization of Obstructive Sleep Apnea in Active-Duty US Military Personnel Receiving Interdisciplinary Care at the National Intrepid Center of Excellence. (25th May 2022) - Hedglen, Erin; Willing, Maegan Paxton; Riley, Mark; Srikanchana, Rujirutana; Moxley, Jasmine; Gottshall, Jackie; Brooks, Peter; Lippa, Sara; Kenney, Kimbra; Pickett, Treven; DeGraba, Thomas; Rhodes, Chandler Sours; et al.
Abstract: Introduction: Among active-duty service members (ADSMs), obstructive sleep apnea (OSA) is associated with decreased quality of life and military readiness/retention. Limited evidence suggests mild traumatic brain injury (mTBI) patients have increased OSA incidence, but little is known about the underlying physiology. This study aims to characterize OSA in treatment-seeking ADSMs with a history of remote mTBI and/or persistent neurobehavioral symptoms to improve detection and early intervention. Methods: This is a retrospective analysis of data collected from ADSMs attending the National Intrepid Center of Excellence Intensive Outpatient Program for persistent symptoms associated with mTBI. Sleep assessment included overnight polysomnography and self-report assessments of sleep quality, somatic and mood symptoms. OSA severity was determined by apnea-hypopnea index (negative: <5, mild: 5-15, moderate/severe: ≥15). Group differences were assessed using analysis of covariance and pairwise least squares regression, controlling for age and body mass index, and corrected for multiple comparisons. Results: Analyses included 574 ADSMs, mostly male (99%), with a mean age of 39.7. The majority (n=288; 50.2%) were OSA negative (OSA-neg); a third had mild OSA (m-OSA) (n=216; 38%); and a tenth were diagnosed with moderate/severe OSA (mod/s-OSA) (n=70; 12%). Mod/s-OSA patients had increased arousal index (p<0.01), hypoxia time (p<0.001), reduced total sleep time (p<0.01) and sleep efficiency (p<0.001) compared to m-OSA and OSA-neg patients. M-OSA patients had an increased arousal index compared to OSA-neg patients (p<0.01). Patient groups did not significantly differ on subjective measures of sleep (i.e., quality, sleepiness), post-concussive, or behavioral health symptoms (anxiety, depression, post-traumatic stress symptoms, alcohol misuse). Conclusion: In our sample of treatment-seeking ADSMs, nearly half presented with OSA according to cut-scores derived for AHI, greater than that expected in the general population. As reported in civilian populations, mod/s-OSA patients demonstrated worse objective sleep measures compared to m-OSA and OSA-neg patients, yet in our sample their self-reported symptom severity did not differ. These findings suggest a low threshold for OSA screening is needed in the symptomatic mTBI population and that multiple factors other than OSA likely contribute to perceived sleep disturbances and neurobehavioral symptoms. Support (If Any): None.